Five-year Outcomes of Ranibizumab in Neovascular Age-related Macular Degeneration: Real Life Clinical Experience - Ozkaya, Abdullah (Korean J Ophthalmol, 2017)
PURPOSE: To evaluate the outcomes of 5-year ranibizumab treatment in neovascular age-related macular degeneration (nAMD) in a single center and real life clinical setting. METHODS: The records of nAMD patients who were treated with ranibizumab between January 2010 and June 2011 were retrospectively reviewed. Patients who completed 5 years of follow-up were included. Main outcome measures were change in best-corrected visual acuity, central retinal thickness, and visit and injection numbers. RESULTS: Forty-four eyes of 37 patients were included. Mean best-corrected visual acuity decreased from 0.82 ± 0.69 to 1.11 ± 0.65 logarithm of minimal angle of resolution after 5 years. Twenty-four eyes (54.5%) had visual acuity loss ≥3 lines, and 20 eyes (45.5%) had stable or improved vision (loss <3 lines, remained stable, or gained ≥1 line) at month 60. The mean total number of visits was 25.3 ± 5.8 (range, 14 to 42), and the mean total number of injections was 12.6 ± 6.4 (range, 3 to 26) at month 60. CONCLUSIONS: Half of the ranibizumab-treated nAMD patients maintained their vision during the 5 years of follow-up. Visit and injection numbers were found to be lower than in prospective studies, reflecting a real world clinical practice.